Interventional Management of Trigeminal neuralgia - Dessy R Emril (Jurnal Kedokteran Syiah Kuala, 2009)
Abstract.   Trigeminal  neuralgia (TN)  is  a  painful neuropathic pain condition  affecting   the face.  It  bas  a significant   impact   on the quality of life and physical function of patients.  Evidence suggests that the likely etiology is vascular compression   of the trigeminal nerve leading to focal demyelination and aberrant neural discharge.  Secondary causes such as  multiple sclerosis  or brain tumors can also produce symptomatic TN. Treatment must be individualized to each patient. Carbamazepine remains the drug of choice in the first-line treatment ~f TN.  Minimal!~ invasive  intervention al pain therapies and surgery. are possible  options when drug therapy  fails.   Younger patients may benefit from microvascular decompression.    Elderly   patients with poorsurgical  risk   may  be   more  suitable  for  percutaneous    trigeminal  nerve  rhizolysis.    The  technique  of radiofrequency rhizolysis of the trigeminal nerve is described in detail in this review.  (JKS2009;2:83-89) Keywords:    imerventional  treatment;  minimally  invasive;  pain   management;  radiofrequencyrhizolysis;trigeminal neuralgia